Inherited disorders and their management in some European warmblood sport horse breeds - Nikolić, Danica (2012)
The main aim of this study was to determine the current strategies employed to manage inherited disorders in European warmblood sport horses. An online survey was sent to 37 breeding organisations in 29 countries, from which 11 countries replied. The breeding associations played major roles in selection, management and recording of inherited disorders. Recording of disorders in both breeding stallions and young horses was practiced in five countries; usually at official events or prior to sale. When disorders of breeding stallions and young horses were recorded during private veterinary visits, there was little obligation to report them. There was a trend for countries with smaller warmblood populations to monitor the fertility of breeding stallions and record disorders in foals. Furthermore, they were more likely to summarise and evaluate records of disorders in breeding stallions and young horses. Evaluation of collected records could be used by breeding associations for the approval of breeding stallions and additionally for advising breeders on more efficient mare-stallion matching. Involvement of all interested parties in the collection and evaluation of these records should be encouraged with the possible creation of a central database for disorders. However, international data collection may not be easy to achieve due to differing classification and diagnoses of disorders or varied scoring systems. This was reflected by the varied consideration of specific disorders in selection of breeding stallions between countries. Regarding management of disorders in breeding stallions, skeletal and joint disorders were screened for the most and muscular disorders the least. Reproductive, respiratory and degenerative joint disorders usually resulted in exclusion from breeding. Most conformational deviations were considered only when severe, or could be compensated for with good performance. These deviations were considered at the same level within countries although research implies that deviations predisposing to injury vary across breeds and sport types. There appears to be a great need for more research into which deviations are most detrimental for riding horses.